2020
DOI: 10.1111/luts.12343
|View full text |Cite
|
Sign up to set email alerts
|

Bladder pain syndrome/interstitial cystitis in contemporary UK practice: Outcomes of phenotype‐directed management

Abstract: Objectives: Problem bladder pain syndrome/interstitial cystitis (BPS/IC) is a heterogeneous disorder with variation in management worldwide. Phenotyping aims to personalize therapy and optimize outcomes. The most well-described phenotype is Hunner lesion disease (HLD). The prevalence of HLD and outcome of phenotypedirected management in the UK is not well-studied. We describe the management of a contemporary cohort of patients with BPS/IC in the UK. Methods: Retrospective analysis of all patients with BPS/IC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This strategy looks to patient-specific symptoms to guide therapeutic decisions and emphasizes collaborative, multi-disciplinary care [92]. Current evidence suggests that phenotype-based treatment plans result in clinically significant improvements in approximately 50% of patients, though re-intervention is often still required [93,94].…”
Section: Interstitial Cystitismentioning
confidence: 99%
“…This strategy looks to patient-specific symptoms to guide therapeutic decisions and emphasizes collaborative, multi-disciplinary care [92]. Current evidence suggests that phenotype-based treatment plans result in clinically significant improvements in approximately 50% of patients, though re-intervention is often still required [93,94].…”
Section: Interstitial Cystitismentioning
confidence: 99%
“…Individual targeted therapy, therefore, is a necessity. The UPOINT phenotypic classification system developed by Shoskes was recommended by CUA, EAU, and two clinical trials [ 9 , 63 , 64 ]. Both studies found that approximately 50% of IC/BPS patients treated with corresponding modalities could achieve significant symptomatic improvements.…”
Section: Treatment Of Ic/bpsmentioning
confidence: 99%